Perfect fluid models of Blanchi type-I in modified Brans-Dicke cosmology - Singh T. (My University, 2025)
The spatially homogeneous and anisotropic Bianchi type-I cosmological solutions of modified Brans-Dicke theory containing barotropic fluid have been obtained by imposing a condition on the cosmological parameter Λ (φ). The particular case when p = ρ has been discussed in detail. © 1984 American Institute of Physics.